2010
DOI: 10.1103/physrevb.82.104519
|View full text |Cite
|
Sign up to set email alerts
|

Surface and bulk electronic structures of LaFeAsO studied by angle-resolved photoemission spectroscopy

Abstract: The electronic structure of LaFeAsO, a parent compound of iron-arsenic superconductors, is studied by angle-resolved photoemission spectroscopy. By examining its dependence on photon energy, polarization, and sodium dosing, both the bulk and the surface contributions are identified. We find that a bulk band moves toward high binding energies below the structural transition temperature, and shifts smoothly across the spin-density-wave transition by about 25 meV. Our data suggest that the band reconstruction may… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
37
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 41 publications
(98 reference statements)
11
37
0
Order By: Relevance
“…Based on Table 1, these two bands are made of the d z 2 and/or d xz orbitals. The ω and ω bands in other iron-based superconductors were found to be made of d z 2 by both experiments and band calculations [13,23], thus here we could attribute them to the d z 2 orbitals as well. However, since the d z 2 orbital is mixed with the d xz orbital in the κ band, there should be a finite mixing of the d xz orbital in these two bands.…”
Section: Electronic Structure Around the Zone Centermentioning
confidence: 97%
See 2 more Smart Citations
“…Based on Table 1, these two bands are made of the d z 2 and/or d xz orbitals. The ω and ω bands in other iron-based superconductors were found to be made of d z 2 by both experiments and band calculations [13,23], thus here we could attribute them to the d z 2 orbitals as well. However, since the d z 2 orbital is mixed with the d xz orbital in the κ band, there should be a finite mixing of the d xz orbital in these two bands.…”
Section: Electronic Structure Around the Zone Centermentioning
confidence: 97%
“…The insulating parental phase even exhibits certain Mott-insulator signatures, and it is phase separated from the superconducting phase in the K x Fe 2−y Se 2 superconductor at a mesoscopic scale [7,10]. Moreover, angle-resolved photoemission spectroscopy (ARPES) studies have shown that its Fermi surface is consisted of electron pockets only [7,11,12], which is again distinct from most of the iron-based superconductors [13][14][15][16][17]. These unique properties of K x Fe 2−y Se 2 have raised a lot of interest.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The above model is capable of quantitatively describing the experimental results measured by ARPES [14,20,[41][42][43][44]. Although the hopping parameters are dominated by t 1s , t 2d , and t 2s , other parameters cannot be ignored.…”
Section: General Properties Of the Modelmentioning
confidence: 99%
“…Density functional theory (DFT) calculations also suggest the formation of 2D surface states on the highly polar surfaces of cleaved LaOFeAs, with electronlike surface band on LaO and holelike surface band on FeAs [33]. Recent ARPES data provide direct evidence for the existence of surface states by showing the lack of k z dispersion for certain bands on cleaved LaOFeAs [34,35].…”
mentioning
confidence: 92%